2006
DOI: 10.1001/archpsyc.63.8.881
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Eating Disorders in At-Risk College-Age Women

Abstract: Among college-age women with high weight and shape concerns, an 8-week, Internet-based cognitive-behavioral intervention can significantly reduce weight and shape concerns for up to 2 years and decrease risk for the onset of EDs, at least in some high-risk groups. To our knowledge, this is the first study to show that EDs can be prevented in high-risk groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
294
2
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(316 citation statements)
references
References 39 publications
11
294
2
7
Order By: Relevance
“…La anorexia nerviosa también ha experimentado un aumento entre las jóvenes en el último tiempo. La edad de inicio promedio para ambos cuadros se estima entre los 15-24 años, lo que coincide con el período de mayores exigencias académicas [17][18] .…”
Section: Introductionunclassified
“…La anorexia nerviosa también ha experimentado un aumento entre las jóvenes en el último tiempo. La edad de inicio promedio para ambos cuadros se estima entre los 15-24 años, lo que coincide con el período de mayores exigencias académicas [17][18] .…”
Section: Introductionunclassified
“…Randomized controlled trials (RCTs) conducted by the original developers of the Body Project support its efficacy and effectiveness in reducing thin-ideal internalization, body dissatisfaction, dieting, negative affect, and ED symptoms, with many effects holding at 1-to 3-year follow-up (Stice, Butryn, Rohde, Shaw, & Marti, 2013;Stice, Chase, Stormer, & Appel, 2001;Stice, Trost, & Chase, 2003;Stice, Marti, Spoor, Presnell, & Shaw, 2008;Stice, Rohde, Butryn, Shaw, & Marti, 2015;Stice, Rohde, Gau, & Shaw, 2009;Stice, Shaw, Burton, & Wade, 2006). Importantly, the Body Project is one of only four interventions shown to reduce the onset of new ED cases (Martinsen et al, 2014;Stice et al, 2008;Taylor et al, 2006), indicating that it truly can prevent at least some EDs. For instance, the Body Project reduced onset of new ED cases by 60% in one trial versus assessment-only control (Stice et al, 2008).…”
Section: The Mission Of the Association For Behavioral Andmentioning
confidence: 99%
“…Although some eating disorder prevention programs show promise in reducing risk (Stice, Marti, Spoor, Presnell, & Shaw, 2008a;Taylor, et al, 2006;Wilksch & Wade, 2009a), maximising the beneficial impact of such programs remains an important endeavour. Eating disorders are characterized by high mortality (Harris & Barraclough, 1998), a destructive physical and psychological course, low rates of presentation to treatment (Johnson, Cohen, Kasen, & Brook, 2002) and comparatively poor treatment outcomes (Steinhausen, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although the selective prevention field has made some important steps in this area (Müller & Stice, 2013;Stice, Marti, Shaw, & O'Neil, 2008b;Stice, Rohde, Gau, & Shaw, 2012;Taylor, et al, 2006), research focus needs to also be directed to moderators of universal interventions in order to understand what might influence the outcome of long-term universal prevention trials. It has been suggested that ideally, eating disorder prevention should operate across a spectrum where pre-and early-adolescents receive empiricallyinformed universal programs where those requiring additional input might later benefit from participation in selective and targeted programs (Neumark-Sztainer, et al, 2006;Wilksch & Wade, 2009b).…”
Section: Introductionmentioning
confidence: 99%